ANALISIS PENINGKATAN PENJUALAN PRODUK MELALUI FAKTOR STRATEGI PEMASARAN PADA PT. MULTI INTI PARAHYANGAN CIREBON - Nurnilasari, Nunung (Exchall, 2019)
Basically every company will always try to continue to maintain the competition so berbagau efforts continue to be done. If the innovation in the sales strategy continues to be developed then the company will be able to evaluate the presence of the products sold. Marketing strategies will be expected to increase the effectiveness of sales of a product. The productivity of the company's profit achievement will increase so that it will guarantee the achievement of the target and the company's suistainability, in this case the company leader must try to give innovation and formulate the strategy of product development starting from input, process and output continuously so that the level of achievement of profit sasran also increase. When the level of product sales is achieved through its marketing strategy, it will encourage them to improve the company's business development towards a better one.In this research which become object of research at PT. Multi Inti Parahyangan Branch Cirebon which engages in the business of consumer good and distributors, on the grounds that the level of competitors are more and more. From the results of the above research can authors conclude as follows: 1. Implementation of the implementation of marketing strategy, the PT.Multi Inti Parahyangan Branch Cirebon can be said to have been good, but still need more improvement. 2. The level of product sales achievement still needs to be improved again this is in line with the emergence of increasingly diverse competitors with almost similar products 3. From the results of correlation test of 0.773 states that the high / strong relationship between sales strategy variables with sales variables. At the real level = 0.05 from the results of the analysis was H: P> 0 received, that is very high correlation, which means between sales strategy variables (X) with sales variable (Y) there is a very high / strong relationship (significant).